Enhanced foamability of isotactic polypropylene composites by polypropylene‐graft‐carbon nanotube. Issue 2 (17th April 2013) - Chen, Chen; Pang, Huan; Liu, Zhong; Li, Yu‐Bao; Chen, Yan‐Hui; Zhang, Wei‐Qin; Ji, Xu; Tang, Jian‐Hua
<x xml:space="preserve">Abstract</x> In this article, utilizing a nucleophilic substitution reaction between epoxy group in polypropylene‐graft‐glycidyl methacrylate (PP‐g‐GMA) and carboxyl groups in oxidized carbon nanotubes (O‐CNTs), PP‐g‐CNT was fabricated for reinforcing the interfacial adhesion between CNTs and polypropylene (PP) matrix, favoring the enhancement of melt strength and elastic modulus, i.e., enhancing the foaming ability of PP composites. Cellular structure and thermo‐mechanical properties of PP foams were characterized by scanning electron microscopy and dynamic mechanical analysis, respectively. The average cell diameter of PP foams decreased from 289.2 (PP‐g‐GMA) to 96.7 μm (PP‐g‐CNT foams with 2.0 wt % O‐CNT) and the distribution of cell size also became more uniform. The storage modulus of PP‐g‐CNT foams increased by nearly 62.5% at −40°C, compared with that of PP‐g‐GMA foams. This work also provided a new procedure for improving the foam ability and thermo‐mechanical property of PP composites. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 961‐968, 2013